2020
DOI: 10.1186/s13561-020-00291-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of health insurance on patient demand for physician services

Abstract: Background In recent years, policymakers have sought to reduce health disparities between the insured and uninsured through a federal health insurance expansion policy; however, disparities continue to persist among the insured population. One potential explanation is that the use of healthcare services varies by the type of health insurance coverage due to differences in the design of coverage. The aim of this study is to examine whether health insurance coverage type is associated with the structure and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We did not include new inpatient or emergency department consultations in our analysis. It has been shown that uninsured patients have a higher probability of utilizing emergency department care than patients with private insurance 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include new inpatient or emergency department consultations in our analysis. It has been shown that uninsured patients have a higher probability of utilizing emergency department care than patients with private insurance 29 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that uninsured patients have a higher probability of utilizing emergency department care than patients with private insurance. 29 Finally, due to EMR limitations, we had to infer binary genders for patients in our data set. We acknowledge that gender is a spectrum and that individuals have their own unique gender identities; because of this, these inferences may have been inaccurate in some cases and have the potential to cause significant harm.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with private and public insurance report higher rates of routine care than uninsured patients, and a lack of health insurance is associated with a lower probability of receiving recommended services that are due during a clinic visit [ 18 , 19 ]. A 2011 study showed the percentage of physicians accepting new patients with Medicaid was lower than the percentage accepting new self-pay, Medicare, or privately insured patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%